Clinical Experience of Bronchoscopy-Guided Radiofrequency Ablation for Peripheral-Type Lung Cancer. (11th September 2013) - Koizumi, Tomonobu; Kobayashi, Takashi; Tanabe, Tsuyoshi; Tsushima, Kenji; Yasuo, Masanori
Abstract : We have developed a new internal cooled electrode for radiofrequency ablation (RFA) (Japan Application no. 2006-88228) suitable for forceps channel bronchoscopy. Here, we present our clinical experience with bronchoscopy-guided RFA under computed tomography (CT) monitoring for patients with peripheral-type non-small-cell lung cancer (NSCLC). Bronchoscopy-guided RFA was performed in two patients (80 and 70 years old) with NSCLC, who had no lymph node involvement and distant metastases (T1N0M0), but not indicated for surgery because of other complications, such as advanced age, poor pulmonary function, and refusal of thoracic surgery. The locations of the tumors were right S2 and left S3, respectively. Although the tumors showed ground-glass opacity (GGO) with solid components in both cases, radiographic findings changed to reduced mass-like shadow and remained stable for 4 and 3.5 years after bronchoscopy-guided RFA. As the former case developed progressive disease on chest CT, bronchoscopy-guided RFA was repeated in the same lesion, resulting in no change for the subsequent 1 year. There were no adverse reactions during the procedures. Thus, bronchoscopy-guided RFA is a safe and feasible procedure that represents a potentially useful therapeutic tool in local control in medically inoperable patients with stage I NSCLC.